The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fnagi.2015.00190
|View full text |Cite
|
Sign up to set email alerts
|

A muscle stem cell for every muscle: variability of satellite cell biology among different muscle groups

Abstract: The human body contains approximately 640 individual skeletal muscles. Despite the fact that all of these muscles are composed of striated muscle tissue, the biology of these muscles and their associated muscle stem cell populations are quite diverse. Skeletal muscles are affected differentially by various muscular dystrophies (MDs), such that certain genetic mutations specifically alter muscle function in only a subset of muscles. Additionally, defective muscle stem cells have been implicated in the pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 192 publications
(256 reference statements)
0
56
0
9
Order By: Relevance
“…Differences in genetic lineage tracers and reagents might explain these discordant 523 results (Matsuoka et al, 2005). Taken together, our findings indicate that connective tissue 524 composition in the neck region correlates with the cellular origin of the associated skeletal 525 components, independently of the myogenic source or ossification mode ( Figure 7D Our study reveals that neck muscles develop in a complex domain that is distinct from the head 543 and trunk ( Figure 7A-D), and that might be a contributing factor to pathologies that affect subsets 544 24 of neck muscles in specific myopathies (Emery, 2002;Randolph and Pavlath, 2015). In human, 545 TBX1 has been identified as a major candidate gene for 22q11.2 deletion syndrome (Papangeli and 546 Scambler, 2013).…”
Section: Connectivity Network Of the Neck And Shoulders 491mentioning
confidence: 60%
“…Differences in genetic lineage tracers and reagents might explain these discordant 523 results (Matsuoka et al, 2005). Taken together, our findings indicate that connective tissue 524 composition in the neck region correlates with the cellular origin of the associated skeletal 525 components, independently of the myogenic source or ossification mode ( Figure 7D Our study reveals that neck muscles develop in a complex domain that is distinct from the head 543 and trunk ( Figure 7A-D), and that might be a contributing factor to pathologies that affect subsets 544 24 of neck muscles in specific myopathies (Emery, 2002;Randolph and Pavlath, 2015). In human, 545 TBX1 has been identified as a major candidate gene for 22q11.2 deletion syndrome (Papangeli and 546 Scambler, 2013).…”
Section: Connectivity Network Of the Neck And Shoulders 491mentioning
confidence: 60%
“…However, under normal physiologic conditions, those muscles do not fatigue or become hypoxic, perhaps explaining their protection from HEO. This variation in skeletal muscles may, in part, be related to the embryonic derivation and gene expression profile of their resident stem cells, (59) and understanding these differences could provide insight into mechanisms underlying the susceptibility of certain muscles to HEO.…”
Section: Discussionmentioning
confidence: 99%
“…However, under normal physiologic conditions, those muscles do not fatigue or become hypoxic, perhaps explaining their protection from HEO. This variation in skeletal muscles may, in part, be related to the embryonic derivation and gene expression profile of their resident stem cells, (59) and understanding these differences could provide insight into We have demonstrated that signaling in FOP lesion formation has a BMP ligand-independent component and is mediated by the SMAD 1/5/8 pathway under hypoxic conditions present in both an injury-induced animal model of FOP and in lesions from FOP patients. However, injury-induced inflammation is a complex physiologic response to damaged tissue, including infiltrating immune cells, progenitor cells, as well as secreted cytokines and chemoattractants.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the functional dynamics of Tbx1 and Isl1 in specific muscles groups will help uncover differences between the ontogenically similar group of CPM derived muscles. Uncoupling the genetic requirements of these distinct populations is necessary to provide a framework that will explain how human myopathies affect only subsets of muscles (Emery, 2002;Randolph and Pavlath, 2015).…”
mentioning
confidence: 99%